Translocation-Specific Conformation of Adenylate Cyclase Toxin from Bordetella pertussis Inhibits Toxin-Mediated Hemolysis - Gray, Mary C. (American Society for Microbiology, 2001)
Bordetella pertussis adenylate cyclase (AC) toxin belongs to the RTX family of toxins but is the only member with a known catalytic domain. The principal pathophysiologic function of AC toxin appears to be rapid production of intracellular cyclic AMP (cAMP) by insertion of its catalytic domain into target cells (referred to as intoxication). Relative to other RTX toxins, AC toxin is weakly hemolytic via a process thought to involve oligomerization of toxin molecules. Monoclonal antibody (MAb) 3D1, which binds to an epitope (amino acids 373 to 399) at the distal end of the catalytic domain of AC toxin, does not affect the enzymatic activity of the toxin (conversion of ATP into cAMP in a cell-free system) but does prevent delivery of the catalytic domain to the cytosol of target erythrocytes. Under these conditions, however, the ability of AC toxin to cause hemolysis is increased three- to fourfold. To determine the mechanism by which the hemolytic potency of AC toxin is altered, we used a series of deletion mutants. A mutant toxin, ΔAC, missing amino acids 1 to 373 of the catalytic domain, has hemolytic activity comparable to that of wild-type toxin. However, binding of MAb 3D1 to ΔAC enhances its hemolytic activity three- to fourfold similar to the enhancement of hemolysis observed with 3D1 addition to wild-type toxin. Two additional mutants, ΔN489 (missing amino acids 6 to 489) and ΔN518 (missing amino acids 6 to 518), exhibit more rapid hemolysis with quicker onset than wild-type toxin does, while ΔN549 (missing amino acids 6 to 549) has reduced hemolytic activity compared to wild-type AC toxin. These data suggest that prevention of delivery of the catalytic domain or deletion of the catalytic domain, along with additional amino acids distal to it, elicits a conformation of the toxin molecule that is more favorable for hemolysis.